Calibration Strategies for Optical Underwater 3D-Scanners - C. Bräuer-Burchardt; R. Ramm; M. Heinze; P. Kühmstedt; G. Notni; G. Notni (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The precise three-dimensional (3D) reconstruction of underwater objects is required in many different applications. Optical systems are gaining popularity due to their high accuracy potential. As a result, calibration of these systems for underwater use is becoming increasingly important. Several approaches for high quality calibration of optical 3D sensors based on stereo cameras are introduced and compared. Because of the transition of the vision rays between the media air, glass, and water, the calibration of optical underwater 3D scanners is challenging. The presented calibration strategies, including expanded advanced pinhole camera modeling, explicit ray refraction modeling, and systematic error compensation by correction functions are described and discussed. The presented strategies provide high accuracy and robustness on the one hand, and practicable usage and pleasant handling on the other hand. Requirements, advantages and limitations of the different strategies are discussed.